Effect of Parasite Diversity on the Levels and Quality of Antibody Responses to Plasmodium Falciparum in an Area of Seasonal Malaria Transmission - Kyei-Baafour, E. (University of Ghana, 2015)
The important role of antibody-mediated mechanisms in protection from clinical malaria has been demonstrated by passive transfer experiments but the targets of protective immunity are not clearly defined. A number of antigens are however in various stages of testing as possible vaccine candidates. Polymorphism in these antigens, which has been reported to be an immune evasion mechanism, has hampered the development of these antigens as vaccines since antibody responses against one allelic form of an antigen have been shown to be less effective against parasites that express a different allele of the same antigen. In animal studies, immunization with a mixture of allelic antigens induced cross-reactive antibodies that had greater and broader in vitro inhibition capacity compared to antibodies induced against the respective single antigens. This study therefore sought to determine the effect of parasite diversity on the levels and quality of antibody responses to P. falciparum in individuals living in an area of seasonal malaria transmission. Indirect ELISA was used to determine total IgG responses to AMA1-3D7, AMA1-FVO, MSP119, CSP, and CelTOS in stored plasma samples taken at two sites, one close to a dam and the other at least 20km away from the dam during the wet and dry season. Competition ELISA was used to determine the relative proportions of cross-reactive and stain-specific anti-AMA1 antibodies. Malaria parasites were detected in participant samples by both microscopy and molecular methods. The study found greater proportion of parasitaemic individuals at the dam site compared to those away from the dam during the dry season (p=0.0061), while proportions were similar in the rainy season. Generally, there were more multiple infections per individual, described as the multiplicity of infection (MOI) in the wet season (60% of participants) compared to the dry season (40.3%, p=0.001). A similar trend was observed when MOI was compared between seasons for the non-dam site (p=0.001), but MOI was similar between the wet and dry seasons at the dam site Antibody levels to sporozoites antigens (CSP and CelTOS) were higher at the dam site compared to the non-dam site, irrespective of the season. No differences between sites were however observed for the blood stage antigens (AMA1 and MSP119). Antibody specificities to multiple AMA1 alleles were observed at sites with MOI greater than 1 and specificity to only the 3D7 allele was observed at sites with single infections. This data generally shows high levels of clinical immunity that is observed in high transmission areas may be associated more with infection by multiple parasite strains (hence a wider breadth of antibody responses) rather than high parasite burden. Consequently low levels of clinical immunity in low transmission areas may be the result of infection with one or a few parasite strains that may induce responses that is not as broad as is seen in high transmission areas.
Thesis (MPhil) - University of Ghana, 2015